Do Transformational Leadership, Interpersonal Communication, and Career Development Have Direct and Indirect Effect on Diplomats’ Organizational Commitment at the Ministry of Foreign Affairs Republic of Indonesia in Jakarta? - Asrarudin; Dedi Purwana; R. Madhakomala (IJHCM (International Journal of Human Capital Management), 2020)
Objective of this research is to determine direct and indirect effects of transformational leadership, interpersonal communication, and career development on the commitment of diplomats at the Ministry of Foreign Affairs of the Republic of Indonesia in Jakarta. The sample design used is probability sampling which provides equal opportunity for each element (member) of the population to be selected as a sample member. And the technique for determining the number of samples is proportionate Stratified Random Sampling. This technique is used because the population is not homogeneous and proportionally distributed. The research design used is a quantitative approach with a total sample of 255 respondents. The data analysis tool used is Structural Equation Modeling (SEM) with WarpPLS 5.0 software. This research reveals that transformational leadership has a positive and significant effect on interpersonal communication which indicates that the better transformational leadership, interpersonal communication will be more increased; transformational leadership has a positive and significant influence on career development which describes that the better transformational leadership, career development will get better; Transformational leadership contributes positively and significantly to organizational commitment through career development which shows an increase in career development then transformation leadership will be better and have an impact on increasing organizational commitment; and interpersonal communication has a positive but not significant role on organizational commitment through career development which shows that good interpersonal communication has neither effect on career development nor impact on the commitment of diplomatic organizations in the Ministry of Foreign Affairs of the Republic of Indonesia.